2019
DOI: 10.12688/f1000research.15512.3
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing malignant mesothelioma survival: a retrospective review of the National Mesothelioma Virtual Bank cohort

Abstract: Background: Malignant mesothelioma (MM) is a rare but deadly malignancy with about 3,000 new cases being diagnosed each year in the US.  Very few studies have been performed to analyze factors associated with mesothelioma survival, especially for peritoneal presentation. The overarching aim of this study is to examine survival of the cohort of patients with malignant mesothelioma enrolled in the National Mesothelioma Virtual Bank (NMVB).   Methods:  888 cases of pleural and peritoneal mesothelioma cases were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…Early diagnosis is so rare that mesothelioma treatment is usually unable to provide a complete cure. Even in early-stage disease, the prognosis remains grim with an overall median survival time of 9–12 months [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Early diagnosis is so rare that mesothelioma treatment is usually unable to provide a complete cure. Even in early-stage disease, the prognosis remains grim with an overall median survival time of 9–12 months [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the results by gender should be handled with care. While gender is known to be a factor influencing mesothelioma survival rates (see e.g., [38]), which may suggest that related death counts may reflect a differential exposure to asbestos, we need to point out that mesothelioma counts are quite low for women and, therefore, the corresponding impact estimate may not be considered as robust as that for men (as suggested by the wider confidence interval). In addition, the results have to be evaluated considering the different latency period between asbestos exposure and mesothelioma or lung cancer occurrence [39][40][41].…”
Section: Discussionmentioning
confidence: 97%
“…In a cancer history classification study, 26 we applied Natural Language Processing (NLP), a modern Artificial Intelligence technique, to automatically classify personal and family history from free-text medical reports of mesothelioma patients, with a high accuracy. In another study, 27 we conducted a retrospective review of the NMVB cohort, and identified factors influencing malignant mesothelioma survival, including age (younger than 45), gender (female), epithelioid histological subtype, staging (I), peritoneal occurrence, and having the combined treatment of surgical therapy with chemotherapy. Moreover, for malignant pleural mesothelioma, we developed a novel computational algorithm that automatically discovered 364 potential protein-protein interactions, of which five interactions (BAP1-PARP3, KDR-ALB, PDGFRA- ALB, CUTA-HMGB1, and CUTA-CLPS) were validated experimentally; our comparative transcriptiome analysis identified five potentially repurposable drugs targeting the interactome proteins (cabazitaxel, primaquine, pyrimethamine, trimethroprim, and gliclazide).…”
Section: Sarcomatoid Mesothelioma Patientmentioning
confidence: 99%